2005
DOI: 10.1051/0004-6361:200500013
|View full text |Cite
|
Sign up to set email alerts
|

The calcium isotopic anomaly in magnetic CP stars

Abstract: Abstract. Chemically peculiar stars in the magnetic sequence can show the same isotopic anomaly in calcium previously discovered for mercury-manganese stars in the non-magnetic sequence. In extreme cases, the dominant isotope is the exotic 48 Ca.Measurements of Ca  lines arising from 3d−4p transitions reveal the anomaly by showing shifts up to 0.2 Å for the extreme cases -too large to be measurement errors. We report measurements of miscellaneous objects, including two metal-poor stars, two apparently normal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Castelli & Hubrig (2004) first announced detection of 48 Ca in several HgMn (CP3) stars. Cowley & Hubrig (2005) subsequently found a similar effect in magnetic Ap (CP2) stars. The shifts appear to vary from those indicating nearly pure 48 Ca to a virtual terrestrial mix (nearly pure 40 Ca).…”
Section: Introductionmentioning
confidence: 64%
“…Castelli & Hubrig (2004) first announced detection of 48 Ca in several HgMn (CP3) stars. Cowley & Hubrig (2005) subsequently found a similar effect in magnetic Ap (CP2) stars. The shifts appear to vary from those indicating nearly pure 48 Ca to a virtual terrestrial mix (nearly pure 40 Ca).…”
Section: Introductionmentioning
confidence: 64%
“…One immediately notices that while the line wings are explained by our calculations, the line core cannot be fitted with the terrestrial Ca isotopic mixture. Cowley & Hubrig (2005) showed that the red-shift of the Ca IR line core arises due to the heavy Ca isotopes and claimed that "in extreme cases the dominant isotope is the exotic 48 Ca".…”
Section: The Ca Isotopic Anomalymentioning
confidence: 99%
“…In addition to remarkable diffusion signatures, recently another Ca anomaly was detected, first in the spectra of the Hg-Mn stars by Castelli & Hubrig (2004) and then in Ap stars by Cowley & Hubrig (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium is an element of considerable interest for many of the cases mentioned above. For example the isotope shift information in the 3d 2 D J → 4p 2 P J infrared triplet [11] led to the discovery of an anomalous isotopic composition in mercury-manganese (HgMn) stars, in which the isotopic Ca ratio in the stellar atmosphere is dominated by 48 Ca [12,13]. Isotope shifts in other calcium transitions have been studied, e.g., to extract nuclear charge radii along the long chain of isotopes [14,15,16,17] or to perform ultra-trace analysis using isotope selective resonance ionization [18].…”
Section: Introductionmentioning
confidence: 99%